An evoluted bio‐based 2, 5‐furandicarboxylate copolyester fiber from poly(ethylene terephthalate). Issue 2 (20th January 2020) - Wang, Peng; Huang, Wei; Zhang, Yajie; Lin, Jinyou; Chen, Peng
ABSTRACT: A series of bio‐based poly(ethylene terephthalate‐ co ‐ethylene 2, 5‐furandicarboxylate) (PEFT) fibers was prepared via the industrially feasible melt‐spinning and hot‐drawing process. The effect of 2, 5‐furandicarboxylic acid (FDCA) content on the fibers properties was studied using differential scanning calorimetry, wide‐angle X‐ray diffraction, sound velocity, tensile, and boiling water shrinkage tests. It was found that the PEFT fibers showed comparable or superior tenacity to the PET fibers under the same conditions, especially the PEFT‐4 fibers exhibited the highest tenacity (2.3, 2.9 cN/dtex for the drawn PET and PEFT‐4 fibers prepared at the same take‐up speed of 2500 m/min and a fixed draw ratio of 1.6). Moreover, the boiling water shrinkage of the PEFT fibers was quite close to that of the PET fibers under the same conditions, showing that the PEFT fibers were comparable to the PET fibers in heat resistance. The results indicated that the bio‐based PEFT fibers would be a feasible alternative for the PET fibers, in terms of sustainability, processability, and mechanical properties. © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 320–329 Abstract : A series of bio‐based PEFT fibers is fabricated via the industrially feasible melt‐spinning and hot‐drawing process and reported for the first time. Owing to the higher total molecular orientation favored by the enhanced spinline tension, the tenacity of the PEFT fibers is found close to or better than that of the PET fibers under the same conditions.